Efektivitas Diversi Dalam Penyelesaian Perkara Anak Yang Berkonflik Dengan Hukum - Imroatus Sholihah; Eva Mar'atus Sholihah; Moh. soleh (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Children in Conflict with the Law (ABH) is an important issue that requires special handling because children have the right to protection, guidance, and self-development. Before the enactment of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA Law), the handling of children's cases tended to follow a retributive system that was retaliatory in nature. The SPPA Law changed this approach by adopting restorative justice through a diversion mechanism. This study aims to analyze the effectiveness of diversion implementation in resolving cases of Children in Conflict with the Law during the investigation stage at the Surabaya City Police Headquarters. This study uses an empirical legal research method (socio-legal research) with a case study and legislation approach. Primary data were obtained through in-depth interviews with key informants, while secondary data came from official documents of the Surabaya City Police Headquarters, diversion minutes, and related literature. Data analysis was conducted using descriptive qualitative methods. The results of the study indicate that the Surabaya City Police have implemented diversion in accordance with the provisions of Articles 7 and 29 of the Juvenile Justice and Child Protection Law (UU SPPA), which must be attempted within a maximum of 7 days from the start of the investigation and a maximum of 30 days for cases with a criminal penalty of under 7 years and non-recidivists. The implementation of diversion involves multi-stakeholder coordination. However, the effectiveness of diversion still faces obstacles, particularly the social stigma against children, which complicates the process of reintegration into society. This study concludes that diversion is an important instrument for realizing a humane juvenile criminal justice system that is oriented towards the best interests of children. Strengthening inter-agency coordination, increasing the capacity of child investigators, and efforts to eliminate social stigma are needed to increase the effectiveness of diversion implementation in the future.